General trends on the impacts of evidence-based university accreditation on quality assurance enhancement - Kairanbayev, Nurali; David, David Arulraj (International Journal of Evaluation and Research in Education (IJERE), 2025)
Traditional accreditation process although has relevant impacts on quality assurance in higher education. Research and practices have shown the value of emerging evidence-based university accreditation. The study therefore aims to understand the impacts of evidence-based university accreditation on quality assurance enhancement. The research relied on literature review and document analysis as suitable methods. The study’s results demonstrated that the final decision for academic accreditation should be based on evidence that all stakeholders took part in quality assurance, namely staff and students. This study also explores the university accreditation practices in the United Kingdom (UK), United Arab Emirates (UAE), and Kazakhstan. The analysis presented here allows us to compare and discuss the practices of three different quality assurance practices. The three cases Quality Assurance Agency for higher education (QAA), Commission for Academic Accreditation (CAA), and Independent Kazakh Agency for Quality Assurance in Education (IQAA) indicate relevant use of evidence-based approaches to university accreditations that support quality assurance enhancement, given the explicit approaches grounded in data and evidence. The future of evidence-based approach will be furthered with the support of technology and sophisticated tools that will support explicit policies and practices. This research is expected to benefit researchers, policy makers and practitioners in quality assurance.